SISTEM PENGHANTARAN OBAT TERTARGET, MACAM, JENIS-JENIS SISTEM PENGHANTARAN, DAN APLIKASINYA - Winarti, Lina (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2013)
Development of methods to improve delivery of drugs for treating dangerous disease like cancer and viral infections are very important today. Selectivity in therapy is needed, hence capability to deliver drugs at specific site being studied in order to reduce toxicity and unwanted side effect at non target site. Many drugs delivery from passive targeting to active targeting delivery will be improved to reach that purpose. Because this system is very important for cancer therapy, many cytotoxic agent have been approved by clinical examination. Besides that targeting drug delivery is very useful for neurological diseases such as alzhemier, liver diseases, kidney, lung, and colon diseases.